Nutritional, physical and sensory properties of extruded products from high-amylose corn grits - Liu, Linsan; Li, Silu; Zhong, Yuyue; Li, Yibo; Qu, Jianzhou; Feng, Jiaojiao; Xu, Shutu; Zhang, Renhe; Xue, Jiquan; Guo, Dongwei (Emirates Journal of Food and Agriculture, 2017)
To investigate the applicability of high-amylose corn grits (HACG) to the process for extruded products, a single screw extruder was used to produce extrudates under feed rate of 220 g/min, barrel temperature of 120°C, and screw rotational speed of 150 rpm. The nutritional, physical and sensory properties were investigated in the HACG extrudate and normal corn grits (NCG) extrudate acting as control. The results indicated that the HACG extrudate had higher (P≤ 0.05) protein (7.07%), fiber (5.41%), lipid (1.48%), ash (0.76%), resistant starch (2.89%), zein (4.65%), calcium (22.34 mg/kg), magnesium (718.63 mg/kg), iron (19.47 mg/kg), zinc (22.73 mg/kg) contents and 16 of 17 types of amino acids compared to the NCG extrudate. In regards to physical properties, the bulk density (BD), radial expansion index (REI) and water solubility index (WSI) values of the HACG extrudate, which were 57.94 mg/ml, 45.47 and 43.25, respectively, were significantly lower (P≤ 0.05) than those of the NCG extrudate. However, the HACG extrudate had a higher special length (SL), indicating a higher axial expansion, water absorption index (WAI), frangibility and cohesiveness (7.34 cm/g, 3.69, 68.79 and 0.32, respectively), and a more sponge-like structure. A sensory analysis indicated that the HACG extrudate had higher values for frangibility, cohesiveness, chewiness and overall taste with a lower coarseness and adhesiveness (to teeth).